Cabotegravir for HIV Prevention in Cisgender Men and Transgender Women - Landovitz, Raphael J; Donnell, Deborah; Clement, Meredith E; Hanscom, Brett; Cottle, Leslie; Coelho, Lara; Cabello, Robinson; Chariyalertsak, Suwat; Dunne, Eileen F; Frank, Ian; Gallardo-Cartagena, Jorge A; Gaur, Aditya H; et al. (The New England journal of medicine, 2021)
Antiviral medication has emerged as an important tool in the prevention of HIV infection. In this randomized, controlled trial, an injectable long-acting agent, cabotegravir, was found to be superior to daily oral tenofovir disoproxil fumarate–emtricitabine in preventing incident HIV infection in cisgender men and transgender women who have sex with men.